Récits de femmes, récits de guerre : un genre problématique - Karen Meschia (Revue LISA)
Taking as its starting point the considerable popular interest in oral history resources in Britain today, and the wide use made of them on the occasion of the 60th anniversary of the end of World War II in a number of institutional and more informal settings, the article briefly retraces the origins of this “history from below”, which frequently involves the use of autobiographical, or self life-writing, in order to question its significance from a gender perspective. After examining in general terms the epistemological and methodological difficulties involved in using oral sources, personal testimony and individual life-histories, the specific problems raised in using women’s narratives are discussed: their traditionally “muted” voice and fragmented sense of selfhood require that new modes of listening and interpretation be brought into play.To bring into focus the practical implications of this theoretical inquiry, the article concludes by looking more closely at how two feminist researchers have made use of women’s accounts of their lives in order to assess the extent to which their experiences during World War II brought about a modification in their status, notably in the articulation between professional and family life.